Rotation Measure Jitter: Wavelength-dependent Scatter in Rotation Measure Related to Faraday Complexity - Jeroen M. Stil (The Astrophysical Journal)
The relation between Faraday rotation measure (RM) and differential Faraday rotation by unresolved structure of a turbulent plasma is investigated for extragalactic radio sources. The RM scatter of a sample of sources affected by turbulent Faraday screens with identical power spectra of Faraday depth structure is referred to as RM jitter. For fixed amplitude and slope of the power spectrum, the range of possible RMs depends on the wavelength coverage of the survey. RM jitter is independent of Faraday depth resolution as it results from the true Faraday depth dispersion and effects of wavelength-dependent depolarization. RM jitter for a flux-density-limited sample is sensitive to the power-law index γ of the power spectrum of Faraday depth structure. Assuming depolarization by a turbulent Faraday screen for all sources, a simulated flux-density-limited sample can reproduce the high RM scatter found by S. Vanderwoude et al. (2024) for sources that are less than 3% polarized. RM jitter of sources that are more than 3% polarized is found to be smaller than the observed scatter, indicating that plasma other than the near-source environment dominates the RM scatter for the more polarized sources. The significance of RM jitter for applications of the RM grid is discussed.